Modularly engineering Rhodotorula toruloides for α-terpineol production - Lyu, Liting; Chen, Qiongqiong; Xue, Haizhao; Mustafa, Sumayya; Manzoor Shah, Aabid; Huang, Qitian; Zhang, Yue; Wang, Shuang; Zhao, Zongbao Kent (Frontiers in Bioengineering and Biotechnology, 2024)
α-Terpineol is a monoterpenoid alcohol that has been widely used in the flavor, fragrance, and pharmaceutical industries because of its sensory and biological properties. However, few studies have focused on the microbial production of α-terpineol. The oleaginous yeast Rhodotorula toruloides is endowed with a natural mevalonate pathway and is a promising host in synthetic biology and biorefinery. The primary objective of this work was to engineer R. toruloides for the direct biosynthesis of α-terpineol. The improvement in monoterpenoid production was achieved through the implementation of modular engineering strategies, which included the enhancement of precursor supply, blocking of downstream pathways, and disruption of competing pathways. The results of these three methods showed varying degrees of favorable outcomes in enhancing α-terpineol production. The engineered strain 5L6HE5, with competitive pathway disruption and increased substrate supply, reached the highest product titer of 1.5 mg/L, indicating that reducing lipid accumulation is an efficient method in R. toruloides engineering for terpenoid synthesis. This study reveals the potential of R. toruloides as a host platform for the synthesis of α-terpineol as well as other monoterpenoid compounds.